2016
DOI: 10.1021/acs.jpca.6b08810
|View full text |Cite
|
Sign up to set email alerts
|

Role of Defects on Regioselectivity of Nano Pristine Graphene

Abstract: Here analytical Fukui functions based on density functional theory are applied to investigate the redox reactivity of pristine and defected graphene lattices. A carbon H-terminated graphene structure (with 96 carbon atoms) and a graphene defected surface with Stone-Wales rearrangement and double vacancy defects are used as models. Pristine sp-hybridized, hexagonal arranged carbon atoms exhibit a symmetric reactivity. In contrast, common carbon atoms at reconstructed polygons in Stone-Wales and double vacancy g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 67 publications
0
24
0
Order By: Relevance
“…The small-molecule nano-graphene self-assembled dynamically to form regular thin sheets, which were sequentially and systematically stacked to form intermittent sheet nano-graphene fragments that were held tightly to each other [43]. On the other hand, the dynamic self-assembled aggregate structure was superimposed on the subject to rearrange/change under stress, thereby forming an uneven gear shape [44, 45]. Owing to the size of the nano-graphene itself, there was no obvious bulge in the overall structure.…”
Section: Resultsmentioning
confidence: 99%
“…The small-molecule nano-graphene self-assembled dynamically to form regular thin sheets, which were sequentially and systematically stacked to form intermittent sheet nano-graphene fragments that were held tightly to each other [43]. On the other hand, the dynamic self-assembled aggregate structure was superimposed on the subject to rearrange/change under stress, thereby forming an uneven gear shape [44, 45]. Owing to the size of the nano-graphene itself, there was no obvious bulge in the overall structure.…”
Section: Resultsmentioning
confidence: 99%
“…The results of this analysis suggest that oxidation of PMCPE occurs via the sulfur atom in the methionine molecule whilst reduction occurs through the carboxylic acid group of the molecule. The Fukui function is generally used to understand redox reaction mechanisms in electrochemistry [2,31]. Simulation based on the Fukui function can be applied in chemical and The Fukui function is generally used to understand redox reaction mechanisms in electrochemistry [2,31].…”
Section: Theoretical Studies Of Methioninementioning
confidence: 99%
“…The Fukui function is generally used to understand redox reaction mechanisms in electrochemistry [2,31]. Simulation based on the Fukui function can be applied in chemical and The Fukui function is generally used to understand redox reaction mechanisms in electrochemistry [2,31]. Simulation based on the Fukui function can be applied in chemical and electrochemical applications for locating electron transfer sites [5,28,[36][37][38].…”
Section: Theoretical Studies Of Methioninementioning
confidence: 99%
See 1 more Smart Citation
“… 21 Assimilation of the surfactant on the surface of the electrode forms an adsorptive layer, which aggregates the electron allocation, enhances the peak current, and amends the redox potential along with changing the stability of electrogenerated intermediates and electrochemical product. 22 , 23 The influence of different surfactants such as sodium dodecyl sulfate (SDS), Triton-X 100 (TX-100), and cetyl trimethylammonium bromide (CTAB) on the redox behavior of AL are studied in this work. It was demonstrated that with a synergistic adsorption mechanism, the cationic surfactant CTAB combines with the substrate in convinced forms and displays distinct enhancement effect on the redox current of AL.…”
Section: Introductionmentioning
confidence: 99%